2011
DOI: 10.4331/wjbc.v2.i3.48
|View full text |Cite
|
Sign up to set email alerts
|

Protease expression by microorganisms and its relevance to crucial physiological/pathological events

Abstract: The treatment of infections caused by fungi and trypanosomatids is difficult due to the eukaryotic nature of these microbial cells, which are similar in several biochemical and genetic aspects to host cells. Aggravating this scenario, very few antifungal and anti-trypanosomatidal agents are in clinical use and, therefore, therapy is limited by drug safety considerations and their narrow spectrum of activity, efficacy and resistance. The search for new bioactive agents against fungi and trypanosomatids has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 115 publications
(143 reference statements)
0
16
0
2
Order By: Relevance
“…Peptidases have emerged as potential targets to the development of new antifungal chemotherapeutics 9 . Several studies have shown that fungal aspartic peptidases are also sensitive to inhibitors produced against HIV used in highly active antiretroviral therapy 13,41,42 . Thus, the ability of these PIs to modulate essential events in fungal cells has been investigated 9,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Peptidases have emerged as potential targets to the development of new antifungal chemotherapeutics 9 . Several studies have shown that fungal aspartic peptidases are also sensitive to inhibitors produced against HIV used in highly active antiretroviral therapy 13,41,42 . Thus, the ability of these PIs to modulate essential events in fungal cells has been investigated 9,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Sources of nitrogen and carbon affect both the constructive synthesis in cultures and the enzyme production [190,191]. Santos and co-workers [184] reported that C. albicans presented a high level of surface Sap1-3 antigens and a high amount of aspartic protease activity secreted into the extracellular environment when Fig.…”
Section: Anti-proliferative Effects Of Hiv Pismentioning
confidence: 99%
“…Analysis of proteolytic enzymes of pathogenic micro-organisms might lead to the design of inhibitors to control these pathogens (Dos Santos, 2011). To colonize a host, fungal micro-organisms have evolved strategies to invade tissues, optimize growth and propagate.…”
Section: Discussionmentioning
confidence: 99%